Antifungal efficacy and mechanisms of Bacillus licheniformis BL06 against Ceratocystis fimbriata - Gao, Fangyuan; Yang, Dongjing; Chen, Jingwei; Zhou, Xiaosi; Zhang, Chengling; Ma, Jukui; Tang, Wei; Liang, Zhao; Wu, Yongwang; Liu, Hongxia; Sun, Houjun (Frontiers in Plant Science, 2025)
Sweet potato black rot caused by the pathogenic fungus Ceratocystis fimbriata is a destructive disease that can result in severe agricultural losses. This study explores the antifungal efficacy and underlying mechanisms of Bacillus licheniformis BL06 against C. fimbriata. The plate antagonism assay revealed that BL06 significantly suppressed the radial growth of C. fimbriata mycelia, achieving inhibition rates of 39.53%, 53.57%, 64.38%, and 69.11% after 7, 10, 13, and 16 days, respectively. In vivo experiments demonstrated that BL06-treated sweet potato tissues exhibited markedly smaller lesions than the control, indicating effective suppression of black rot. Microscopic observations indicated that BL06 treatment altered the morphology and activity of C. fimbriata mycelia, causing swelling and deformation. Additionally, BL06 markedly reduced spore production and germination in a dose-dependent manner, with complete inhibition observed at the highest concentrations tested. The cell-free supernatant (CFS) of BL06 was identified as the primary antifungal agent, achieving an inhibition rate of 76.11% on mycelial growth. Transcriptome analysis of C. fimbriata treated with BL06 CFS revealed significant downregulation of genes involved in cell wall and membrane biosynthesis, spore development, protein processing in the endoplasmic reticulum, and energy metabolism. These findings suggest that BL06 is a potent biocontrol agent against C. fimbriata, exerting its effects through multiple molecular pathways.